Implementação de um quadrotor como plataforma de desenvolvimento para algoritmos de controle - Melo, Alexandre Secchin de (2010)
This work aims the implementation of a unmanned, four-rotor miniature flying machine as a development platform, part of a long term research. The final goal, yet to be achieved, is the realization of a flying object with maximum practicable degree of autonomous decisions based on the on-board sensory and computational power, control strategy and assigned task. Up to this work, it consists of a low cost electro-mechanical hardware, whose electronic part allows the implementation of an 8-bit microcontroller-based, MEMS accelerometer and gyroscopes, allows the implementation of a generic fly control for attitude stabilization. The broad spectrum of applications includes: the inspection of various kinds of environments such as electric power transmission lines, police surveillance of woods and hard-to-reach places with sky sight for fugitive detection, crops and herd monitoring, as well as film takings for the cinematographic and real estate industries. Tests undertaking so far with the prototype suggest the successful implementation of a fly attitude controller.